An intensive, structured, mobile devices-based healthcare intervention to optimize the lipid-lowering therapy improves lipid control after an acute coronary syndrome - Ruiz-Bustillo, Sonia; Badosa, Neus; Cabrera-Aguilera, Ignacio; Ivern, Consol; Llagostera, Marc; Mojón, Diana; Vicente, Miren; Ribas, Núria; Recasens, Lluis; Martí-Almor, Julio; Cladellas, Mercè; Farré, Núria (Frontiers in Cardiovascular Medicine, 2022)
Aims Despite the evidence, lipid-lowering treatment (LLT) in secondary prevention remains insufficient, and a low percentage of patients achieve the recommended LDL cholesterol (LDLc) levels by the guidelines. We aimed to evaluate the efficacy of an intensive, mobile devices-based healthcare lipid-lowering intervention after hospital discharge in patients hospitalized for acute coronary syndrome (ACS). Methods and results Ambiespective register in which a mobile devices-based healthcare intervention including periodic follow-up, serial lipid level controls, and optimization of lipid-lowering therapy, if appropriate, was assessed in terms of serum lipid-level control at 12 weeks after discharge. A total of 497 patients, of which 462 (93%) correctly adhered to the optimization protocol, were included in the analysis. At the end of the optimization period, 327 (70.7%) patients had LDLc levels ≤ 70 mg/dL. 40% of patients in the LDLc ≤ 70 mg/dL group were upgraded to very-high intensity lipid-lowering ability therapy vs. 60.7% in the LDLc > 70 mg/dL group, p < 0.001. Overall, 38.5% of patients had at least a change in their LLT. Side effects were relatively infrequent (10.7%). At 1-year follow-up, LDLc levels were measured by the primary care physician in 342 (68.8%) of the whole cohort of 497 patients. In this group, 71.1% of patients had LDLc levels ≤ 70 mg/dL. Conclusion An intensive, structured, mobile devices-based healthcare intervention after an ACS is associated with more than 70% of patients reaching the LDLc levels recommended by the clinical guidelines. In patients with LDLc measured at 1-year follow-up, 71.1% had LDLc levels ≤ 70 mg/dL.